2021
DOI: 10.3390/e23121591
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Resting-State Functional Complexity in Elderly with Subjective Cognitive Decline

Abstract: Individuals with subjective cognitive decline (SCD) are at high risk of developing preclinical or clinical state of Alzheimer’s disease (AD). Resting state functional magnetic resonance imaging, which can indirectly reflect neuron activities by measuring the blood-oxygen-level-dependent (BOLD) signals, is promising in the early detection of SCD. This study aimed to explore whether the nonlinear complexity of BOLD signals can describe the subtle differences between SCD and normal aging, and uncover the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…These brain regions with altered activity intensity were primarily associated with the executive (SFG&CPL), language (IPL&CPL), and motor (SFG&IPL) functions. Previous studies have indicated that sALFF increased in the SFG region for CSVD patients (Dong et al, 2021;Ni et al, 2021;Pelkmans et al, 2019;Pena et al, 2019;Ren et al, 2023;Su, Wang et al, 2019;Wang et al, 2015), consistent with our findings. SFG is a core brain region for executing many cognitive tasks and motor control (Li et al, 2013;Wang et al, 2019).…”
Section: F I G U R E 4 Results Of the Relationship Between Dynamic Am...supporting
confidence: 93%
“…These brain regions with altered activity intensity were primarily associated with the executive (SFG&CPL), language (IPL&CPL), and motor (SFG&IPL) functions. Previous studies have indicated that sALFF increased in the SFG region for CSVD patients (Dong et al, 2021;Ni et al, 2021;Pelkmans et al, 2019;Pena et al, 2019;Ren et al, 2023;Su, Wang et al, 2019;Wang et al, 2015), consistent with our findings. SFG is a core brain region for executing many cognitive tasks and motor control (Li et al, 2013;Wang et al, 2019).…”
Section: F I G U R E 4 Results Of the Relationship Between Dynamic Am...supporting
confidence: 93%